The Gambia : Article IV Consultation, Third Review under the Extended Credit Facility Arrangement, Request for Waivers of Nonobservance of Performance Criteria, and Financing Assurances Review-Press Release; Staff Report; and Statement by the Executive Director for The Gambia. (IMF Staff Country Reports; Country Report, 2021)
Prior to the onset of the pandemic, The Gambia had shown strong macroeconomic performance in the few years following the remarkable political transition in 2016-17. Economic growth accelerated, debt vulnerabilities decreased, external stability strengthened, structural and legislative reforms advanced, and key social indicators improved. However, the COVID-19 pandemic halted some of the hard-won progress, stagnating economic activity and re-igniting extreme poverty. The Gambia experienced a third wave of the pandemic in mid-2021, which has receded recently. The COVID-19 vaccination rate currently stands at about 12 percent of the adult population. Presidential and parliamentary elections are planned for December 2021 and April 2022, respectively.